2018
DOI: 10.1002/arch.21450
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of posterior silk gland of Bombyx mori during spinning period and the role of PI3K/Akt pathway

Abstract: Bombyx mori is an economic insect of the Lepidoptera. Its posterior silk gland (PSG) is an important organ for fibroin synthesis. In order to study the occurrence of apoptosis in PSG and the role of PI3K/Akt signaling pathway during spinning period, changes in morphology of silk gland, expressions of fibroin components Fib-H, Fib-L and P25 and Akt, TOR2, P70S6K and S6 in PI3K/Akt pathway, expressions of apoptosis related genes caspase-3, caspase-9 and activity of caspase-3 were explored. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This signalling pathway in fact represents the mediator that leads to the activation of autophagy at metamorphosis via nutrient signals and hormones, at least in the larval fat body [5]. Furthermore, a recent study has reported that the expression of apoptosisrelated genes, such as caspases, during the spinning period is regulated by PI3K/Akt, suggesting a possible role of this signalling pathway in activating apoptosis in the posterior silk gland of B. mori, too [80]. However, further investigation is needed to confirm this hypothesis for the PI3K/Akt pathway and, hopefully, to characterize the putative regulatory mechanism.…”
Section: (E) Cross-talk Between Autophagy and Apoptosismentioning
confidence: 99%
“…This signalling pathway in fact represents the mediator that leads to the activation of autophagy at metamorphosis via nutrient signals and hormones, at least in the larval fat body [5]. Furthermore, a recent study has reported that the expression of apoptosisrelated genes, such as caspases, during the spinning period is regulated by PI3K/Akt, suggesting a possible role of this signalling pathway in activating apoptosis in the posterior silk gland of B. mori, too [80]. However, further investigation is needed to confirm this hypothesis for the PI3K/Akt pathway and, hopefully, to characterize the putative regulatory mechanism.…”
Section: (E) Cross-talk Between Autophagy and Apoptosismentioning
confidence: 99%
“…19,25 Apart from the above advantages, SF has a synergistic effect with HA on PI3K/Akt activation. 26,27 Some previous reports have shown the applications of SF 28 and HA 29 as a surface coating on TIs under normal culture conditions. However, to our knowledge, there have been no reports demonstrating the promotive effect of SF/HA hybrid coatings under diabetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, hydroxyapatite (HA) as a component of natural bone tissue has excellent osteoinductivity and biodegradability, which could be slowly replaced as a bone repair and replacement material . It has been demonstrated that the incorporation of HA in SF scaffolds may promote bone regeneration through the osteoinductive effects of HA on osteogenic cells, exerting better osteoconductivity and osteoinductivity than SF alone. , Apart from the above advantages, SF has a synergistic effect with HA on PI3K/Akt activation. , Some previous reports have shown the applications of SF and HA as a surface coating on TIs under normal culture conditions. However, to our knowledge, there have been no reports demonstrating the promotive effect of SF/HA hybrid coatings under diabetic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It also helps maintain body growth and development, organ remodeling and cellular immunity. [1][2][3] Apoptosis is also involved in resisting virus invasion and maintaining body stability. 4 For example, the human body protects against influenza A virus (IAV) infection by regulating apoptosis.…”
Section: Introductionmentioning
confidence: 99%